Should adult ventilated patients on the intensive care unit be fasted preoperatively?. (2nd April 2021) - Pandya, Shivani J; Spiro, Michael
Abstract : In the absence of separate guidelines for critically unwell ventilated patients in the intensive care unit who are undergoing surgery, questions arise about whether patients in intensive care should be starved preoperatively, despite already having a protected airway.